(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
Single photon emission computed tomography, SPECT, has been proven reliable in imaging radiotracer distribution inside an opaque system. Due to the limited number of detection tools available, an assessment and comparison are made for different detection arrangement in developing an industrial SPECT system (iSPECT) which can be utilized for imaging in industrial condition. In the present study, hexagonal, octagonal and nonagonal iSPECT arrangements were modelled and simulated using MCNPX code. The detection system only used a maximum number of 36 lead collimated sodium iodide, NaI scintillation detector. The reconstructed images for single point-source and two point-source are evaluated and compared for all three systems. The result shows of the three iSPECT arrangement, the nonagonal system has the best image resolution and ability to detect the single and two point-source position inside the region of interest.